Cardiac Arrhythmia: Atrial Flutter in a Newborn. Case Study - T.M. Klimenko; O.Yu. Karapetyan; A.N. Zakrevsky; Ye.A. Serdtseva; O.S. Karatay; I.V. Soloshenko; O.P. Melnychuk (Zaslavsky O.Yu., 2014)
The article gives case report of rare in neonatal period cardiac arrhythmia - atrial flutter. The disease is one of the manifestations of life-threatening heart rhythm disorders, has no characteristic clinical picture, is diagnosed only by means of an electrocardiogram.